Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Cinnamon Hotel Butique Syariah Bandung - Sukriadi, Erie Hidayat; Mulyani, Ade Nisya (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2024)
This study aims to determine the Influence of Facilities and Service Quality on Customer Satisfaction at Cinnamon Hotel Boutique Syariah Bandung, this study was conducted by distributing questionnaires to 100 respondents. The research method uses a quantitative method using multiple linear regression tests, with questionnaire data collection techniques, observation and literature studies. where the independent variables are facilities and service quality, and the dependent variable is customer satisfaction. data processing using SPSS software. The results showed that the facility variable had a positive and significant effect on customer satisfaction, while the service quality variable had a significant and positive effect on customer satisfaction. simultaneously (simultaneously) had a positive and significant effect. The coefficient of determination or R² value was (76.8%), and the rest (23.2%) was influenced by other variables outside this study.